Diversification, risk, and performance: Do the type of family and state ownership matter? - Jul Aidil Fadli (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — This study aims to examine the roles of the ultimate owners, i.e., family and state, as moderating factors on the relationships between bank diversification, risk, and performance. To capture different aspects of diversification, we consider bank income, loan, deposit, and asset diversifications.Method — The data analysis technique employed in this research is multiple regression in the form of pooled regression. The data were sourced from the financial statements of 53 banks in Indonesia. It is worth noting that the data used in this study comprise panel data, which combines time series and cross-sectional data. This utilization of panel data serves to increase the depth of observation in the research.Result — Income diversification provides benefits to banks in the form of risk reduction and performance improvement. On the other hand, loan, deposit, and asset diversifications have a negative impact on banks by enhancing risks and degrading performance. Furthermore, ownership of the bank by the family and the state negatively impacts income diversification, possibly due to the lack of ultimate expertise, which results in limitations in transferable skills. In contrast, ownership of the bank by the family can weaken the positive effects of loans and assets.Contribution — This study provides significant insights into the development of banking research, offering a more comprehensive measure of diversification in terms of income, loans, deposits, and assets. Moreover, this study measures bank ownership through ultimate ownership, which can reveal the actual ownership of the bank.